PENGARUH AGENCY COST TERHADAP KINERJA KEUANGAN PADA PERUSAHAN MANUFAKTUR ( STUDI PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR CONSUMER AND GOOD YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2014 - 2017 ) - Hidayat, Andri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This research aims to examine the effect of Agency Cost on the financial performance of manufacturing companies. The objects of this research are manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange between 2014 and 2017. 39 data are collected through Tobin’s Q method with the agency cost proxy of insider ownership, dispersion ownership, and institutional ownership. The multiple linear regression analysis applied in this research indicates that insider ownership partially has a positive and significant effect on company value; dispersion ownership partially has a negative and significant effect on company performance; and institutional ownership partially has a positive and significant effect on company value.Keywords: agency cost, manufacturing companies, insider ownership, dispersion ownership, institutional ownership, Tobin’s Q